Compressive Strength and Water Absorption of Pervious Concrete that Using the Fragments of Ceramics and Roof Tiles - Prahara E. (EPJ Web of Conferences, 2014)
Pervious concrete was introduced in America in 2003, popularized by Dan Brown and used as a rigid pavement in the open parking lot. Rigid pavement using pervious concrete can absorb water in the surface to go straight through the concrete to the ground below.This water flow is one of the benefit of using the pervious concrete. Using of wastes such as broken roof and ceramics tiles are not commonly used in Indonesia. Utilization these kind of wastes is predicted lower the compressive strength of pervious concrete as they are used as a substitute for coarse aggregate.In this research, pervious concrete is made using a mixture of the fragment of ceramics and roof tiles.This research using broken ceramics and roof tiles with a grain size that loose from 38 mm sieve, retained on 19 mm sieve and the coarse aggregate from crushed stone that loose 12.5 mm sieve, retained on 9.5 mm sieve. The water cement ratio is 0.3 and to assist the mixing process, the addition of addictive in pervious concrete is used.The size of coarse aggregate used in the mixture affects the strength of pervious concrete. The larger the size of aggregate, the obtained compressive strength becomes smaller. It also affects the density of pervious concrete. The using of mixture of ceramics and roof tiles only reduce 2 MPa of pervious concrete compressive strength so this mixture can be used as a substitute for coarse aggregate with a maximum portion of 30 %. The high porosity of the specimens causes the reduction of pervious concrete density that affect the compressive strength. This high level of porosity can be seen from the high level of water absorption that exceed the required limit of water infiltration.